Analyse economique de la consommation du bois de feu en regions forestieres: lecons des zones urbaines camerounaises - Nkamleu, G.B.; Endamana, D.; Gockowski, J.; Ndoye, O.; Sunderlin, William D. (2002)
This paper aims at analyzing fuel consumption in households of forest zones, and at showing the place of fuelwood as a source of energy in the region. The study was carried out in Cameroon and it was based on a survey done in 1996. A sample of 400 households from Yaounde, Mbalmayo and Ebolowa was used. The results obtained confirm the importance of fuelwood, in its different forms, as a source of energy in urban areas. This importance is higher in less urbanized town, while the spatial repartition of the others sources of energy (kerosne, gas) is reserved. Finally, the econometric analysis, using of Engel's curves allowed the elasticity of income to be assessed, showing a negative link between income levels and fuelwood consumption.